Fatality rates associated with driving and cycling for all road users in Great Britain 2005–2013. (March 2018) - Scholes, Shaun; Wardlaw, Malcolm; Anciaes, Paulo; Heydecker, Benjamin; Mindell, Jennifer S.
Abstract: Fatality rates based on deaths only to the drivers themselves do not accurately portray the impact of driving on road traffic deaths. We characterised more fully the impact of driving and cycling on road traffic fatalities by including deaths to all the other road users in fatal car or cycle crashes. We used crash data from the Great Britain National Road Accident Database (STATS19) and exposure data from the National Travel Survey. Rates were estimated as the ratio of fatalities to the amount of time travelled: fatalities per million hours' use (f/mhu). Rates in 2005-07, 2008-10, and 2011-13 were calculated based on deaths to: (1) the drivers or cyclists themselves (persons 'in charge' of vehicles), (2) other, i.e. 'third-party', road users (e.g. passengers, drivers or riders of other vehicles, and pedestrians), and (3) both of these groups combined, i.e. all road users. Rates were stratified by the sex and age of the drivers or cyclists involved in the fatal crashes. Rates based on deaths to persons in charge of vehicles were higher for cyclists than for drivers, whereas those based on deaths to third-party road users showed the opposite. The inclusion of third-party deaths increased the overall rates considerably more for drivers than for cyclists. Nevertheless, the overall rate for male cyclists (2011-13: 0.425 f/mhu; 95% Confidence Interval (CI): 0.377–0.478) exceeded that for male drivers (0.257 f/mhu; 95% CI: 0.248–0.267). A similar pattern was observed for females (cycling: 0.216 f/mhu; 95% CI: 0.158–0.287; driving: 0.127 f/mhu; 95% CI: 0.120–0.135). These differences between cars and cycles were overestimated as the safer travel on motorways could not be disaggregated in the estimates for driving. The higher rates for cycling - mainly borne by the cyclists themselves - need to be balanced against the substantially lower risks to other road users. Highlights: Fatality rates based only on drivers do not portray the full impact of driving Full accounts require including deaths to all other road users in fatal car crashes Most deaths in car crashes were to non-drivers, especially for young male drivers Fatality rates based on all road users were higher for driving than for cycling Higher rates for cyclists however co-occur with lower rates for other road users